A Case of Stercoral Perforation Detected on CT Requiring Proctocolectomy in a Heroin-Dependent Patient. (18th October 2016) - Seligman, William H.; Alam, Fahreyar; Planner, Andy; Alexander, Roderick J.
Abstract : Stercoral perforation of the colon is rare but carries with it significant morbidity and mortality. Stercoral perforation usually occurs in elderly, immobile patients with chronic constipation. In this manuscript, we report the case of stercoral perforation in a patient due to chronic heroin dependence. We report the case of a 56-year-old male patient with stercoral perforation, diagnosed by computed tomography, secondary to heroin dependence, requiring proctocolectomy and an end ileostomy. There are very few reports in the literature describing cases of stercoral perforation and questions have been asked about the importance of preoperative cross-sectional imaging. In our case, the diagnosis of stercoral perforation was made only on CT. Although this is not the first such case to be reported, it is significant as preoperative CT imaging was influential not only in determining the aetiology of the abdominal distension seen on the plain film, but also in detecting the pneumoperitoneum which was not evident clinically or on plain radiographs.